Correlation Between Diet History and Nutritional Status of Children Aged 24–59 Months in Tarumajaya, Bekasi in 2019 - Nasution, Lailan Safina; Karim, Nursakinah A. (Jurnal Gizi dan Pangan, 2024)
This study aimed to analyze the correlation between diet history and the nutritional status of pre-school children. This was an analytical observational study using a cross-sectional design. Sam-ples were 96 children aged 24‒59 months in Tarumajaya, Bekasi, West Java. Diet history was obtained from questionnaires containing history of breastfeeding and diet since the infancy period. The children’s heights were measured using a microtoise stature meter. Subjects were considered stunted if their Height-for-Age Z-score was minus 2 or lower according to WHO Child Growth Standard. Data was analyzed using Fisher’s exact test. Out of the 96 children, 16 (16.7%) were stunted. There were 80 (83.3%) children who received exclusive breastfeeding, 51 (53.1%) who received an appropriate frequency of meals, 78 (81.3%) who met the minimum dietary diversity, and 29 (30.2%) who had a minimum acceptable diet. Fisher’s exact test showed that dietary diversity was a significant factor for stunted children (p<0.001).